To solve, use the substitution method.
4x + 5y = -12
Move the variable to the right and change sign.
4x = -12 - 5
Divide both sides of the equation by 4.
x = -3 - 5/4y
Substitute the given value of x into the lower equation.
-2 (-3 - 5/4y) + 3y = -16
Distribute -2 through the parenthesis.
6 + 5/2y + 3y = -16
Add like terms.
6 + 11/2y = -16
Use inverse operations to multiply both sides by 2.
12 + 11y = -32
Move the constant to the right side.
11y = -32 - 12
Solve.
11y = -44
Divide both sides by 11.
y = -4 (your answer)